Sekrety samurajow ; studium o japonskich sztukach walki - Ratti, Oscar; Westbrook, Adele; Matusiak, Marek (Bydgoszcz : Diamond Books, 1997)
Polish translation of "Secrets of the Samurai". A study of Japanaese military science and of the Samurai.
Includes bibliographic refeences (p. 393-398).
Keywords: Military art and science; Samurai